Normative Data for Gait Speed and Height Norm Speed in ≥ 60-Year-Old Men and Women - Kasović M (Dove Medical Press, 2021)
Mario Kasović,1,2 Lovro Štefan,1 Andro Štefan1 1Faculty of Kinesiology, Department of General and Applied Kinesiology, University of Zagreb, Zagreb, 10000, Croatia; 2Faculty of Sports Studies, Department of Sport Motorics and Methodology in Kinanthropology, Masaryk University, Brno, 62500, Czech RepublicCorrespondence: Lovro ŠtefanFaculty of Kinesiology, Department of General and Applied Kinesiology, University of Zagreb, Horvaćanski Zavoj 15, Zagreb, 10000, CroatiaTel +385-09891-77-060Email lovro.stefan1510@gmail.comPurpose: To determine normative data for gait speed and height-normalized gait speed in community-dwelling older men and women.Materials and Methods: In this cross-sectional study, we recruited 565 men and women aged ≥ 60 years old. Age was calculated from the date of birth and further classified into four categories: (1) 60– 65 years, (2) 66– 70 years, (3) 71– 75 years and (4) ≥ 76 years. Gait speed was assessed by a pressure platform (ZEBRIS, Munich, Germany) in meters per second (m/s). Height and weight were objectively measured. Height-normalized gait speed was calculated by dividing gait speed by height. We created the 20th, 40th, 60th and 80th percentile curves for both outcome measures using Cole’s Lambda (L), Mu (M) and Sigma (S) method.Results: Mean gait speed and height-normalized gait speed was 1.24 (standard deviation 0.28) and 0.75 (0.17). Significant age-related decline in gait speed for both sexes was observed (p < 0.001). Being a woman (β = - 0.09, p < 0.001), being older (β = - 0.02, p < 0.001) and having higher body mass index values (β = - 0.02, p < 0.001) were significantly associated with slower gait speed.Conclusion: Gait speed significantly declines with age in both older men and women. Providing normative data can be used in screening and monitoring “slow” walkers to prevent from foot pain and higher risk of falls.Keywords: walking, elderly, standards, ageing